Pengembangan E-Modul PAI Menggunakan Kvisoft Flipbook Maker pada Materi Sholat Jenazah di SMPN 6 Kinali Pasaman Barat - Aria Aria; Wedra Aprison (YASIN, 2026)
The development of digital learning media in Islamic Religious Education has received attention in various previous studies. However, studies that specifically develop e-modules based on Kvisoft Flipbook Maker for funeral prayer material at the junior high school level remain limited. This study aims to develop an Islamic Religious Education e-module using Kvisoft Flipbook Maker for funeral prayer material for Grade VIII students at SMP Negeri 6 Kinali, West Pasaman, and to determine the level of validity of the resulting product. This study used a quantitative approach with the Research and Development (R&D) method through the Four-D (4-D) development model, which includes the define, design, and develop stages. The research participants consisted of material expert validators, media experts, language experts, and Grade VIII students at SMP Negeri 6 Kinali, West Pasaman, selected using purposive sampling. Data were collected through observation, interviews, documentation, validation sheets, and questionnaires, and were then analyzed using quantitative descriptive analysis in the form of mean scores and feasibility percentages. The findings show that the developed e-module obtained a very valid category, making it feasible for use as a learning medium for funeral prayer material. The resulting product integrates material, images, instructional videos, and practice questions in the form of an interactive flipbook that can be accessed through computers and smartphones. The conclusion of this study affirms that the development of an e-module based on Kvisoft Flipbook Maker can serve as an alternative digital learning medium that supports the presentation of Islamic Religious Education material in a more interactive and student-centered manner. The implications of this study contribute to the development of digital learning media in Islamic Religious Education subjects and expand the use of Kvisoft Flipbook Maker as an interactive teaching material. Future research is recommended to test the effectiveness of the e-module across broader material coverage and subjects.